(untitled) (Cultura Económica, 2019)
The Anglosphere, Northern Europe and the Sinosphere are conglomerates of countries that include populations that manifest the highest degree of pro-market ideology. These nations tend to have institutions that are conducive to economic efficiency. Following F. Hayek’s intuition, this paper presents the hypothesis that the capitalist mentality of these countries originates in their historical agrarian structures, given that they all included many economic agents accustomed to actively interacting in the market without strong restrictions. This situation generated an understanding and acceptance of the operation and virtues of competitive economies. In the rest of the world, by contrast, a large part of the rural population was marked by feudal constraints or suffered from strong communal, tribal, and governmental interference; another part were proletarians or slaves in large plantations or haciendas. This condition provoked passivity in laborers, since they perceived their actions to be limited to a large extent by other agents or organizations. This passivity translated into a mentality that had a higher propensity for the acceptance of government intervention.